Hubungan Persepsi Siswa Mengenai Pembelajaran Bauran dengan Motivasi Belajar Siswa pada Mata Pelajaran Biologi - Ade Suryanda; Eka Putri Azrai; Nesya Sabrina Rahmadani (Biopedagogia, 2022)
The spread of Covid 19 in Indonesia has made the government implement online learning. The application of online learning has obstacles that result in ineffective learning. In February 2022 the government re-implemented face-to-face learning with 50% capacity. Online learning and face-to-face learning are combined for today's learning which is also known as mixed learning. Mixed learning as a solution during a pandemic in learning activities. In the process of learning biology, motivation is needed to achieve learning objectives. Learning motivation is influenced by several factors, one of which is students' perceptions of the learning mix. The purpose of this study was to determine the relationship between students' perceptions of mixed learning and students' learning motivation in biology subjects. This research uses a correlational study method. The population of this research is the students of SMA Negeri 54 Jakarta with a total sample of 114 students of class X MIPA who were selected through the Simple Random Sampling. The results of the study revealed that there was a positive relationship between students' perceptions of mixed learning and students' learning motivation in biology subjects. The level of relationship is included in the moderate criteria, therefore, to increase student learning motivation not only by increasing student perceptions but many other factors that influence, because learning motivation can arise from within the individual (intrinsic) and from outside the individual (extrinsic).Â Â Keywords: blended learning, learning motivation, student perception